Effectiveness of Melatonin for the Prevention of Intensive Care Unit Delirium. Issue 3 (23rd March 2019) - Baumgartner, Laura; Lam, Kalvin; Lai, Jonathan; Barnett, Mitch; Thompson, Ashley; Gross, Kendall; Morris, Amanda
Abstract : Study Objective: Intensive care unit (ICU) delirium is an acute brain dysfunction that has been associated with increased mortality, prolonged ICU and hospital lengths of stay, and development of post‐ICU cognitive impairment. Melatonin may help to restore sleep and reduce the occurrence of ICU delirium. The purpose of this study was to evaluate the effectiveness of melatonin for the prevention of ICU delirium in critically ill adults. Design: Retrospective, observational cohort study. Setting: Large academic medical center. Patients: A total of 232 adults were included who were admitted to the medical‐surgical or cardiac ICUs between 2013 and 2017 who had a negative Confusion Assessment Method for the ICU (CAM‐ICU). Of those, patients who received melatonin for at least 48 hours were included in the melatonin group (n=117). Patients were included in the control group if they were admitted to the ICU for at least 4 days (average time of melatonin initiation) and did not receive melatonin or antipsychotics within the first 4 days of their ICU stay (n=115). Measurements and Main Results: The primary outcome was development of delirium, which was assessed by using the CAM‐ICU twice daily by nursing staff. The development of delirium was significantly lower in the melatonin group: 9 (7.7%) versus 28 (24.3%) patients (p = 0.001). This finding remained significant in multivariate logistic models controlling for age, sex, history of hypertension, need for emergent surgery, Acute Physiology and Chronic Health Evaluation II score, mechanical ventilation, ICU length of stay, dexmedetomidine use, and benzodiazepine use. For those patients who developed delirium, patients in the control group had, on average, 20.9 delirium‐free days without coma in 28 days compared with 19.9 days in the melatonin group (p = 0.72). In the melatonin group, melatonin was used for a mean ± SD of 6.3 ± 7.9 days, with a median dose of 3.5 mg/night (range: 1–10 mg). Conclusion: The development of ICU delirium was significantly lower in the melatonin group compared with that in the control group. To our knowledge, this is one of the only studies that has examined the use of melatonin for the prevention of ICU delirium. Melatonin may be a promising agent for the prevention of ICU delirium; however, a randomized study is needed to further validate its efficacy.